Rights of Minorities in Islamic Society - Islami, Abohanifa (Journal of Social Sciences - Kabul University, 2023)
The term minorities does not exist in the Islamic dictionary and literature, Rather, it is a new term imported from Western countries, which wants to interfere with Islam and Islamic societies and object to them, as if the rights of minorities are being violated in Islamic societies. The holy religion of Islam does not recognize the term minority, nor does it treat and interact with minorities (non-Muslims) as minorities, but treat the minorities (non-Muslims) in Islamic societies as the residents of the same country which are mentioned in Islamic texts as: “. Dhimmis, Mustaman”. Interaction and behavior, We have many examples of this interaction throughout history, It is clear from this that Islam and all the rights of non-Muslims living in the Islamic society are protected, such as, nonMuslims have freedom of belief and religion in Islamic countries, they have freedom and authority in performing their worship and so on. Their lives, honor and wealth are protected and finally, in the Islamic society, non-Muslims enjoy all the rights and privileges that a single.